Roles of School Based Management Committee on Girl-Child Access to Primary Education in Kaduna State, Nigeria - Jemimah Jatau; Muhammad Mustapha Jagaba; Murtala Akanbi Yusuf (The University of Kuningan, 2021)
This study examined the roles of School Based Management Committee on Girl Child Access to Primary Education in Kaduna State, Nigeria. Cross-sectional survey design was adopted and School Based Management Committee Roles Questionnaire (SBMCRQ) was the instrument used to collect data. The sample size of 759 respondents comprising of 378 teachers and 381 SBMC members from 346 primary schools in Kaduna State using multi-stage sampling technique was used. A total of 759 copies of the questionnaire were given out to the respondents and 717 copies were returned after the administration. There was 94.5% rate of return. The instrument was validated by experts. The Cronbach alpha reliability for the SBMCRQ is 0.85. The data collected were analyzed with the use of frequency and percentages as well as mean and standard deviation. It was found that activities of School Based Management Committee in Kaduna State in terms of sensitizing the general public about importance of girl-child education, advocacy visits to community stakeholders, awareness creation and regular engagement and interaction with religious leaders with a view to do away with misconception about education of female children have yielded positive results in terms of increase of girl child’s access, enrolment, retention and completion of primary education. It was recommended that School Based Management Committee should be made more functional in all primary schools in Kaduna State. The Government at the State level should intensify supervision and inspection of schools to ensure that SBMC is more effective and maintains positive relationships with teachers for excellent girl-child access to primary education.